Answers
Answered by
2
Heya User ✌
Here's your answer friend,
_________________________________
==> 2x² - 3x + 5 = 0
==> 2x² - 5x + 2x + 5 = 0
==> x(2x - 5) - 1(2x - 5) = 0
==> (x - 1)(2x - 5) = 0
==> x = 1 or x = 5/2
__________________________________
HOPE IT HELPS YOU :)
#BEBRAINLY
#TOGETHER WE GO FAR
#☺☺☺
Here's your answer friend,
_________________________________
==> 2x² - 3x + 5 = 0
==> 2x² - 5x + 2x + 5 = 0
==> x(2x - 5) - 1(2x - 5) = 0
==> (x - 1)(2x - 5) = 0
==> x = 1 or x = 5/2
__________________________________
HOPE IT HELPS YOU :)
#BEBRAINLY
#TOGETHER WE GO FAR
#☺☺☺
Similar questions
Social Sciences,
8 months ago
Accountancy,
8 months ago
Physics,
8 months ago
Math,
1 year ago
Biology,
1 year ago
English,
1 year ago
Science,
1 year ago